PENDIRIAN RUMAH IBADAT DI KOTA CIREBON PASCA PEMBERLAKUAN PERATURAN BERSAMA MENTERI AGAMA DAN MENTERI DALAM NEGERI NOMOR 9 DAN 8 TAHUN 2006 - M. Agus Noorbani (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
After determination of the joint regulation between minister of religious affairs and home affairs No.9 and 8, 2006 (PBM number 9 and 8, 2006), it does not cause the conflicts in establishing the worship house. Many studies examine the establishment of many worship houses that cause conflicts in society. This case study design with qualitative approach explores the process of renovation of GKI Kebon Cai in Cirebon after PBM No. 9 and 8,2006 is determined. This study finds that the religious and community leaders play a major role in mobilizing the citizens to support renovation committee as one of requirements to issue the building permit (IMB) for the worship house.